PENGEMBANGAN INSTRUMEN SENSITIVITAS LINGKUNGAN DALAM RANGKA PENINGKATAN WAWASAN LINGKUNGAN GURU PAUD DI WILAYAH JAKARTA - SUNARYO, SUNARYO; ISTIADI, YOSSA (Program Studi Magister Pendidikan Anak Usia Dini, 2017)
The objectivity of research is to develop the instrument of environmental sensitivity which have influence to increase environmental view for PAUD teachers. Research and development method taken through by need analysis, instrument draft, validation, and wide test of the instrument. Result, there are build a standardize of instrument through two cycles validation about 10 items instrument from 20 items. Also with the one factor of varian analysis in threes areas in Jakarta such as, Jatinegara District, Pasar Minggu District, and Grogol District, that F value 2,94 (p>0,01), there are not significant difference (Ho rejected). Based on that, a instrument have taken to recommendation. Keywords: Environmental sensitivity, Environmental View, PAUD teacher